Public Data Literacy and Integrated Statistical Services: A Case Study of Badan Pusat Statistik Bengkulu Province - Riki Musben; Jeri Andika Saputra; Tika Susanti; Siska Yona Melati; Nada Soraya; Rekho Adriadi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
Data literacy has become an essential competency in the digital era, particularly in supporting evidence-based decision-making. However, public understanding and utilization of statistical data remain limited, especially at the local level. This study examines the role of Integrated Statistical Services (Pelayanan Statistik Terpadu/PST) at Badan Pusat Statistik Bengkulu Province in supporting public data literacy. A qualitative participatory approach was employed, involving internship-based community engagement through observation, service assistance, and user education activities. Data were collected through field observations and interactions with service users and were analyzed descriptively to identify patterns in user engagement and comprehension. The findings indicate that PST functions not only as a data access point but also as an informal learning space that facilitates users’ understanding of statistical information. Student involvement in service assistance contributed to more interactive communication and improved user engagement with statistical data. However, the extent of literacy improvement remains context-dependent and requires further systematic measurement. This study highlights the potential of PST as a supportive platform for enhancing public data literacy, while emphasizing the need for more structured evaluation and standardized literacy indicators in future research.